Keys, phylogenies and biogeography of Polypedilum subgenus Uresipedilum Oyewo et Saeher (Diptera, Chironomidae) - Sæther, Ole A.; Oyewo, Emmanuel Adeoye (Zootaxa, 2008)
Keys to the males of the 48 known species of the subgenus Uresipedilum Oyewo et Sæther of Polypedilum Kieffer, and of the known pupae and larvae are presented. P. (U.) chubetudeeum Sasa et Suzuki is regarded as a synonym of P. (U.) aviceps Townes. Parsimony analyses show that the subgenus can be divided into four tentative main groups: the cultellatum group, the pedatum group, the albicorpum group, and the convictum group. Brooks parsimony analyses (BPA) and Bremer estimate was used to assess the geographic co-evolution and make comparisons with other subgenera. Dispersal via a Beringian connection between East Asia and the Nearctic Region is clear with further dispersal south to Guatemala and Peru more tenuous. There also are indications of connections between the Afrotropical region, South and East Asia, Australia and New Zealand. This may be direct dispersal by mean of floating detritus rather than Gondwanian vicariance as Polypedilum is common on several oceanic islands. The same distribution patterns are apparent in other subgenera as well as in other basal Chironomini. However, while there are no clear indication of vicariance between the Neotropical and Afrotropical regions in Uresipedilum such vicariance is evident in the subgenera Tripodura Townes and Cerobregma Oyewo et Sæther as well as in Nilothauma Kieffer.